1984
DOI: 10.1111/j.1432-1033.1984.tb08015.x
|View full text |Cite
|
Sign up to set email alerts
|

Activation of ATPase of spinach coupling factor 1. Release of tightly bound ADP from the soluble enzyme

Abstract: Several seemingly unrelated procedures used to elicit the latent ATPase activity of soluble spinach coupling factor 1 can be correlated to the release of tightly-bound ADP from the uncoupled enzyme. This ADP release is further enhanced by the presence of medium nucleotides, especially substrate ATP, and may or may not involve release from the catalytic site itself. Similarly, the light/dithiothreitol activation of membrane-bound CF, ATPase is reported to be accompanied by energy-dependent ADP dissociation. Fur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

1986
1986
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 40 publications
1
2
0
Order By: Relevance
“…Several studies also confirmed that both activation and ADP release can be caused by membrane energization (i.e. by pmf-driven rotation of subunit ␥) (27)(28)(29)(30)(31)(32)(33)36). The results shown in Figs.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…Several studies also confirmed that both activation and ADP release can be caused by membrane energization (i.e. by pmf-driven rotation of subunit ␥) (27)(28)(29)(30)(31)(32)(33)36). The results shown in Figs.…”
Section: Discussionsupporting
confidence: 57%
“…Single molecule experiments revealed that ADP inhibition results in long pauses in enzyme turnover (23) and that the rotation of subunit ␥, caused by either external forces or thermal fluctuations, relieves ADP inhibition (26). It was also demonstrated that the tightly bound inhibitory ADP can be expelled by pmf (19,(27)(28)(29)(30). This phenomenon underlies the so-called "activation by pmf," that is, the increase in ATPase activity of the enzyme after membrane energization (31)(32)(33)(34)(35)(36).…”
mentioning
confidence: 99%
“…This appears not to be the case here, since sulfite stimulates even when the Mg2+ concentration is below inhibitory levels. Alcohols are known to stimulate chloroplast coupling factors from spinach (35) and Chlamydomonas reinhardii (22). In spinach chloroplasts, alcohols seem to function by enhancing the release of tightly bound ADP.…”
Section: Downloaded Frommentioning
confidence: 99%